Brain-Based Learning in Islamic Education: Integrating Neuroscience, Intellect, and Spirituality - Ihsan; Ahmad Lahmi; Dasrizal Dahlan; Rosniati Hakim (Suria Academic Press, 2026)
The advancement of neuroscience has contributed significantly to contemporary educational discourse, particularly in understanding how the brain processes information, regulates emotions, and supports learning activities. This study aims to examine the integration of neuroscience and Islamic educational perspectives in developing holistic learning strategies. Using a qualitative approach with a library research design, this study analyzes various classical and contemporary sources related to educational neuroscience, brain-based learning, and Islamic educational thought. The findings indicate that learning is a complex neurobiological process influenced by neuroplasticity, emotional conditions, memory systems, and environmental stimulation. Neuroscientific principles such as contextual learning, multisensory instruction, active participation, and emotionally supportive environments are highly relevant for improving educational effectiveness. Furthermore, Islamic educational concepts concerning ‘aql (intellect), tafakkur (reflection), and insan kamil (holistic human development) demonstrate substantial compatibility with modern neuroscience. The study also reveals that the integration of neuroscience and Islamic values can strengthen educational practices by combining cognitive, emotional, moral, and spiritual dimensions simultaneously. Therefore, neuroscience-informed Islamic education offers a holistic and humanistic educational framework capable of producing learners who are intellectually competent, emotionally resilient, spiritually grounded, and ethically responsible. This integration is expected to contribute to the development of adaptive and transformative educational models in addressing the challenges of twenty-first-century education.